Beef cattle systems analysis - R.R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1986)
For cattle producers to stay in business, they must apply the business management techniques used by sophisticated non-agricultural enterprises. Among these techniques is systems analysis, in which formulas representing interrelationships between various inputs are built into a computer program. The program simulates expected results, based on available information.
Keywords: Cattlemen& #x27; s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Management techniques; Cattle